Read-back improves information transfer in simulated clinical crises. Issue 12 (11th August 2014) - Boyd, Matt; Cumin, David; Lombard, Braam; Torrie, Jane; Civil, Nina; Weller, Jennifer
Abstract : Background: Safe and effective healthcare is frustrated by failures in communication. Repeating back important information (read-back) is thought to enhance the effectiveness of communication across many industries. However, formal communication protocols are uncommon in healthcare teams. Aims: We aimed to quantify the effect of read-back on the transfer of information between members of a healthcare team during a simulated clinical crisis. We hypothesised that reading back information provided by other team members would result in better knowledge of that information by the receiver than verbal response without read-back or no verbal response. Method: Postanaesthesia care unit nurses and anaesthetic assistants were given clinically relevant items of information at the start of 88 simulations. A clinical crisis prompted calling an anaesthetist, with no prior knowledge of the patient. Using video recordings of the simulations, we noted each time a piece of information was mentioned to the anaesthetist. Their response was coded as read-back, verbal response without read-back or no verbal response. Results: If the anaesthetists read back the item of information, or otherwise verbally responded, they were, respectively, 8.27 (p<0.001) or 3.16 (p=0.03) times more likely to know the information compared with no verbal response. Conclusions: Our results suggest that training healthcare teams to use read-back techniques could increase information transfer between team members with the potential for improved patient safety. More work is needed to confirm these findings.